Do Health Technology Assessment organisations consider manufacturers’ costs in relation to drug price? A study of reimbursement reports - Joost J. Enzing; Saskia Knies; Jop Engel; Maarten J. IJzerman; Beate Sander; Rick Vreman; Bert Boer; Werner B. F. Brouwer (Cost Effectiveness and Resource Allocation, 2022)
Abstract Introduction Drug reimbursement decisions are often made based on a price set by the manufacturer. In some cases, this price leads to public and scientific debates about whether its level can be justified in relation to its costs, including those related to research and development (R&D) and manufacturing. Such considerations could enter the decision process in collectively financed health care systems. This paper investigates whether manufacturers’ costs in relation to drug prices, or profit margins, are explicitly mentioned and considered by health technology assessment (HTA) organisations. Method An analysis of reimbursement reports for cancer drugs was performed. All relevant Dutch HTA-reports, published between 2017 and 2019, were selected and matched with HTA-reports from three other jurisdictions (England, Canada, Australia). Information was extracted. Additionally, reimbursement reports for three cases of expensive non-oncolytic orphan drugs prominent in pricing debates in the Netherlands were investigated in depth to examine consideration of profit margins. Results A total of 66 HTA-reports concerning 15 cancer drugs were included. None of these reports contained information on manufacturer’s costs or profit margins. Some reports contained general considerations of the HTA organisation which related prices to manufacturers’ costs: six contained a statement on the lack of price setting transparency, one mentioned recouping R&D costs as a potential argument to justify a high price. For the case studies, 21 HTA-reports were selected. One contained a cost-based price justification provided by the manufacturer. None of the other reports contained information on manufacturer’s costs or profit margins. Six reports contained a discussion about lack of transparency. Reports from two jurisdictions contained invitations to justify high prices by demonstrating high costs. Conclusion Despite the attention given to manufacturers’ costs in relation to price in public debates and in the literature, this issue does not seem to get explicit systematic consideration in the reimbursement reports of expensive drugs.